ORGANOLEPTIC OF FOOD PRODUCTS MADE FROM GUDE BEAN (Cajanus cajan) - Alwi Smith; Kristin Sangur (EDU SCIENCES JOURNAL, 2021)
The use of local bean as an alternative food to meet the community's nutritional needs has been widely practised by society. One of the popular local beans in Kisar Island, Southwestern Maluku community, is gude bean. The people of Kisar Island have used gude beans and sweet potatoes to make traditional food, namely kolak (sweet compote), while the young pods are used as fresh vegetables. Gude bean can be used as a functional food such as gude essence, sweetened condensed milk, and soy sauce. The research objective was to determine the organoleptic assessment of food products from gude beans. Three sterile food products using gude beans were made in this research. The organoleptic tests were conducted on the Kisar community. Organoleptic panellists were fifteen (15) people originally from Kisar Island who live in Ambon city. Panellists were selected using a purposive sampling technique because they originally from Kisar Island know the nature of gude beans, like gude beans, have consumed gude beans. Descriptive analysis techniques were used as data analysis. The results showed that gude essence, milk, and soy sauce products had good taste, colour, texture, and aroma and were acceptable for consumption. This organoleptic test showed that the Kisar community could accept the gude bean food products.